TEACHING AND LEARNING SCIENCE: STUDENTS’ PERSPECTIVE - Rohandi Rohandi (IJIET (International Journal of Indonesian Education and Teaching), 2017)
There is widespread concern for the situation of school science regarding contents and teaching methods. In this study, based on open questionnaire data, we explore Indonesian students’ difficulties and their learning preference in science at two secondary schools students. In this paper how students perceive science as a subject and how the science instruction are expected to happened in classroom setting are described and discussed. Based on findings, the teaching of science needs to be emphasized more on the relevancies to students’ experiences and on knowledge in context.